Some Methodological Considerations for the relationship between Environmental Degradation, Economic Growth and Energy Consumption for South Asian Countries - Jadoon, Atif Khan; Sarwar, Ambreen; Qasim, Hafiz Muhammad; Javaid, Maria Faiq; Liaqat, Saima; Ahmed, Munazza (International Journal of Energy Economics and Policy, 2022)
The present study is designed to investigate that how Economic Growth (EG) of the South Asian region has affected the Environmental Degradation (ED) from 1980 to 2018. This study has used Newey and West (1987) robust standard errors approach to overcome the problem of autocorrelation and heteroskedasticity in panel data. The results of the statistical model confirmed the existence of the Inverted U-shaped Environmental Kuznets Curve (EKC). Furthermore, the results also confirmed that the use of energy is also deteriorating the environment significantly. One significant contribution of the study is to check the causality between EG and CO2 by applying a relatively new approach namely Granger non-causality test presented by Dumitrescu and Hurlin (2012). The results confirmed that economic growth is contributing towards more CO2 emissions. The study concluded that South Asian countries should use environment-friendly renewable energy sources to achieve a higher growth rate.